Analisa Kemudahan Penggunaan Aplikasi Pengajuan Praktik Kerja Mahasiswa Berbasis Web Pada Universitas Budi Darma Menggunakan Framework Cobit 5 - Teddy Erlambang; Muhammad Luthfi Akbar; Mesran (ADA Research Center, 2023)
Work practice is an activity for students in the world of work both in government and in companies, work practice is a required subject for students to complete. This work practice aims to give students work experience before they enter the real world of work. The information system for submitting work practices at Budi Darma University is a web-based application that is implemented so that it can assist in submitting students who will carry out work practices. The Budi Darma University website is an online service facility that students can use to get general information about lecture activities at Budi Darma University. Easy access to this web-based application can be measured with the COBIT 5 framework.Control Objective for Information and Related Technology (COBIT) is a work scheme or best practice management and information technology to help balance the balance between technical problems in IT, control needs and business risks. The results obtained from this study are that the COBIT 5 framework can measure the ease of use of applications for submitting web-based student work practices. Where the level of Capability Level in current conditions is at level 3(Established Process) which means that the system has been operating properly and on target. It can be said that web-based applications at Budi Darma University have not reached the expected conditions, namely at level 4(Predictable Process) with the gap figure (GAP) that is owned, namely 1.3.